SOSIALISASI PENGEMBANGAN PRODUK OLAHAN STROBERI BAGI UKM DI DESA SEMBALUN KABUPATEN LOMBOK TIMUR - Yuliandari, Rini; Nuada, I Wayan (Devote: Jurnal Pengabdian Masyarakat Global, 2024)
Sembalun Village, East Lombok District is a strawberry producing village. Strawberries are a typical souvenir of this area. Excessive and poorly distributed harvest result in wasted strawberries which are ultimately only used as animal feed and fertilizer. So there is a need for product development starting from various types of processed strawberry products to quality packaging so that they can be marketed more widely. The method for implementing this activity begins with observing and identifying problems, and providing an initial solution, namely in the form of outreach regarding the development of processed strawberry products for SMEs in Sembalun Village, East Lombok Regency. The socialization regarding the development of processed strawberry products that we carry out includes providing examples such as processed strawberry jam, strawberry chips, strawberry nuggets, and several other types of processed strawberry products, good packaging and we also socialize about digital marketing to SMEs in Sembalun Village, East Lombok. The outreach given to SMEs and farmers in Sembalun Village is expected to products with packaging according to standards and an understanding of digital business. This socialization provides new understanding to SMEs and farmers in Sembalun Village in developing product innovation and business management so as not to reply on conventional methods, so that in terms of management, marketing, finance and other fields they can increase development more quickly.